Multifuncionalidad rural y percepción social en el País Vasco: un reconocimiento pendiente - Alberdi Collantes, Juan Cruz (Geographicalia, 2014)
The plans of rural development of the Basque Country lean in their natural, landscaping and productive potentialities directed to urban habitant who lives in the proximity. The appreciation of the quality of the rural area by the society, therefore, is fundamental for the progress of the countryside and implicitly supposes the recognition of the multifunctionality of this environment. The urban habitant, nevertheless, although appreciates the natural area of the rural spaces does not know the function of the farmer in the conservation with the exception of the farm activity. The rural development has to happen through the social recognition and for it is necessary to inform and to educate all the society.
Keywords: rural development; public opinion; rural multifunctionality; Basque Country.